Himalayas : ecology and environment / edited by S. K. Chadha - S. K. Chadha (ed.) (Delhi, 1988)
The chief object of the present volume, is to create environmental consciousness among the public. An honest effort has, therefore, been made to touch all the vital issues of Himalayan ecology and environment.
Keywords: Soil erosion Himalayas